Décrire et gouverner l’opinion. Pour une phénoménologie de la correspondance publique de Machiavel - Landi, Sandro (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (CRRS, Victoria University, 2009)
Despite its status as archival source, the public correspondence of Machiavelli has rarely been studied by historians. This essay offers an analysis of this source from the viewpoint of the history of political communication. Usually focussing on the means of transmission, studies on political communication generally fail to address the question of the ontological status of public opinion and its relationship to truth: it is precisely this point that concerns us first of all. We then propose to study communication practices in a defined historical and historiographical context, namely, the construction of the state in modern Italy, understood as both territorial control and conflict management. Machiavelli’s correspondence captures the practical dimension of doxa in a twofold context: that of diplomatic mission, which requires the construction and transmission of truth, and the government of the territory, which requires constant attention both to current rumours and the changing moods of the subject populations.